Why Are There So Few Schumpeterian Entrepreneurs from China? Understanding the Factors That Influence Entrepreneurial Opportunity Evaluation from a Comparative Culture Perspective - Li, Yuanqing; Rosenbloom, Al (Journal of Comparative International Management)

(untitled) (Management Futures, 2024)
Opportunity evaluation is a very important part of entrepreneurial activity; however, entrepreneurs’ individual differences in evaluating opportunities have been neglected in prior research. To address this gap, we apply institutional theory and stereotype threat theory to explain how some institutional factors differentiate entrepreneurs’ opportunity evaluation process. More specifically, we explore how external institutional factors, such as political and social factors, along with personal institutional factors, such as family influences, affect the opportunity evaluation of entrepreneurs under various cultural backgrounds, specifically China and the United States. The Schumpeterian entrepreneur, in which radical innovation and the desire to significantly upend market equilibria, frames our discussion. This paper contributes to the theoretical understanding of the factors influencing entrepreneurial opportunity evaluation from a comparative culture perspective and to the comparative international entrepreneurship field by building a comparative evaluation framework that summarizes institutional factors influencing Chinese and American entrepreneurs’ opportunity evaluation. We propose that policy, social value, and belief as well as family will have significant impacts on entrepreneurs’opportunity evaluation. We further propose several cultural constructs such as individualism vs. collectivism, uncertainty avoidance, and Confucian work dynamism will moderate the relationship with institutional factors in influencing an entrepreneur’s opportunity evaluation process. We discuss our implications with attention given to how our comparative evaluation framework provides insights into why China and the United States differ in terms of developing Schumpeterian entrepreneurs. We then discuss the framework’s limitations.